2020
DOI: 10.3390/toxins12090592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Ochratoxin A and Fumonisin Profiles of Strains of Aspergillus Section Nigri Isolated from Dried Vine Fruits

Abstract: We investigated ochratoxin A (OTA) contamination in raisin samples purchased from Slovak markets and determined the diversity of black-spored aspergilli as potential OTA and fumonisin (FB1 and FB2) producers. The taxonomic identification was performed using sequences of the nuclear ITS1-5.8s-ITS2 region, the calmodulin and beta-tubulin genes. We obtained 239 isolates from eight fungal genera, of which 197 belonged to Aspergillus (82%) and 42 strains (18%) to other fungal genera. OTA contamination was evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
0
6
0
1
Order By: Relevance
“…According to Esteban et al (2006) , up to 6% of A. niger strains synthesise the mycotoxin ochratoxin A, and its degree of production depends on environmental factors, such as the substrate or cultivation medium type, cultivation time, etc. Foodborne A. niger strains are also able to produce the mycotoxins fumonisins, namely fumonisin B1 and B2 ( Noonim et al, 2009 ; Mikušová et al, 2020 ). The cultivation medium notably affects fumonisin synthesis, as is the case with ochratoxin A production ( Frisvad et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Esteban et al (2006) , up to 6% of A. niger strains synthesise the mycotoxin ochratoxin A, and its degree of production depends on environmental factors, such as the substrate or cultivation medium type, cultivation time, etc. Foodborne A. niger strains are also able to produce the mycotoxins fumonisins, namely fumonisin B1 and B2 ( Noonim et al, 2009 ; Mikušová et al, 2020 ). The cultivation medium notably affects fumonisin synthesis, as is the case with ochratoxin A production ( Frisvad et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, all four strains isolated from dried grapes sold in the Slovak food market belonging to A. niger were found to produce fumonisin B 1 (FB 1 ) and FB 2 , while other Aspergillus section Nigri isolates, including Aspergillus welwitschiae , A. carbonarius , and Aspergillus tubingensis , were not capable of producing fumonisins [ 66 ]. In Greece, FB 2 was found in 12 out of 42 raisin samples (29%) at levels of 7.1–25.5 μg/kg, 6 of which co-occurred with OTA [ 31 ].…”
Section: Mycotoxin Profile In Dried Fruitsmentioning
confidence: 99%
“…Similarly, another study reported that the OTA content in the dried vine fruit ranged between 0.8 and 10.6 μg/kg. However, the tolerable concentration posed by the European Commission was 10 μg/kg (Mikušová et al., 2020). Further, variation in the levels of OTA in dried vine fruits varied across the regions.…”
Section: Mycotoxins In Fruit and Fruit Productsmentioning
confidence: 99%